Pengaruh Perkembangan Teknologi terhadap Minat Baca Siswa UPT SPF SD INPRES Manggala: Penelitian - Rudianto Tallu Lembang; Bellona Mardhatillah Sabillah; Cayati; Baharuddin Hafid (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of technological developments on reading interest in students at UPT SPF SD Inpres Manggala. This research is an ex post facto study using a quantitative approach. This research took place at UPT SPF SD Inpres Manggala, Makassar City. The sample in this study were students in grade V, with a total sample of 37 students, while the sampling technique used simple random sampling. The data collection method for sampling used questionnaires and documentation, with data analysis using SPSS 21.0. The results of the descriptive statistical analysis with an average value of technology use of 3.459 with an interval value of 65-80 were in the very influential category. Meanwhile, students' reading interest is seen from the average value of the results of 3.378 with an interval value of 50-64 with a percentage of 51.4% in the high category. The results of the inferential analysis show a positive influence of the learning environment on creative thinking skills with a Sig value of 0.000 according to the specified criteria Sig (0.000) ≤ (0.05) so that H0 is rejected and H1 is accepted. Based on the results of the research that has been conducted, it can be concluded that technological developments have a very high influence on students' reading interest at the UPT SPF SD Inpres Manggala.